Assisted query formulation using normalised word vector and dynamic ontological filtering - Dreher, Heinz; Williams, Robert (Springer-Verlag, 2006)
Information seekers using the usual search techniques and engines are delighted by the sheer power of the technology at their command ? speed, quantity. Upon closer inspection of the results, and reflection upon the next stages of the information seeking knowledge work, users are typically overwhelmed, and frustrated. We propose a partial solution by focusing on the query formulation aspect of the information seeking problem. First we introduce our version of a semantic analysis algorithm, named Normalised Word Vector, and explain its application in assisted query formulation. Secondly we introduce our ideas of supporting query refinement via Dynamic Ontological Filtering.